2023
DOI: 10.5114/biolsport.2023.110747
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combining HIIT and dry-land training on strength, technique, and 100-m butterfly swimming performance in age-group swimmers: a randomized controlled trial

Abstract: Combined interventions of pool-based and dry-land workouts are a common practice in swimming training. However, the effects on strength, technique and swimming performance are still not clear. Through a randomized controlled trial study, we investigated the effect of combining high intensity interval training (HIIT) and maximum strength training (MST) on strength, technique and 100-m butterfly swimming performance. Competitive age-group swimmers (N = 22, males) were randomly divided into two groups. The experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…These results are in line with Faude et al [11], who showed that four weeks (six sessions per week) of high-volume training (64.78 ± 23.7 km) did not improve the performance of 100 and 400 m front crawls (p > 0.05) in competitive swimmers (age = 16.6 ± 1.4 years). Similar findings stated in several previous studies show that to optimize swimming performance, it is recommended that the intervention periods should last more than four weeks of training [8,19]. For instance, Amara et al [8] noted that a period of eight weeks of training with a total training volume of 201 km could optimize the performance of 100 m butterfly (3.56%) in young competitive male swimmers (age = 14.10 ± 0.30 years).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…These results are in line with Faude et al [11], who showed that four weeks (six sessions per week) of high-volume training (64.78 ± 23.7 km) did not improve the performance of 100 and 400 m front crawls (p > 0.05) in competitive swimmers (age = 16.6 ± 1.4 years). Similar findings stated in several previous studies show that to optimize swimming performance, it is recommended that the intervention periods should last more than four weeks of training [8,19]. For instance, Amara et al [8] noted that a period of eight weeks of training with a total training volume of 201 km could optimize the performance of 100 m butterfly (3.56%) in young competitive male swimmers (age = 14.10 ± 0.30 years).…”
Section: Discussionsupporting
confidence: 58%
“…Similar findings stated in several previous studies show that to optimize swimming performance, it is recommended that the intervention periods should last more than four weeks of training [8,19]. For instance, Amara et al [8] noted that a period of eight weeks of training with a total training volume of 201 km could optimize the performance of 100 m butterfly (3.56%) in young competitive male swimmers (age = 14.10 ± 0.30 years).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…These results suggested that the swimming behavior in mice is hardly trainable. Similarly, the swimming skill is not likely to be improved if there is no intended training in humans ( Smith et al, 2002 ; Amara et al, 2023 ). However, some mice exhibited positive swimming behavior adaptations to long-term training.…”
Section: Discussionmentioning
confidence: 99%